Development of a semi selective medium for isolating Xanthomonas camprestris pv. musacearum from insect vectors, infected plant material and soil - Mwangi, M.; Mwebaze, M.; Bandyopadhyay, Ranajit; Aritua, Valentine; Eden-Green, S.; Tushemereirwe, Wilberforce K.; Smith, J. (Wiley, 2007)
A semiselective medium was developed for isolating Xanthomonas campestris pv. musacearum (Xcm) from infected banana plants, soil and insect vectors. The new medium was named cellobiose-cephalexin agar (CCA) and it contained (L−1): 1 g yeast extract, 1 g glucose, 1 g peptone, 1 g NH4Cl, 1 g MgSO4•7H2O, 3 g K2HPO4, 1 g beef extract, 10 g cellobiose, 14 g agar, 40 mg cephalexin, 10 mg 5-fluorouracil and 120 mg cycloheximide. The medium was evaluated for selectivity using 21 bacterial isolates and for plating efficiency using Xcm. The bacterial isolates included a soilborne Xanthomonas species and three pathogenic Xanthomonas strains that infect cassava, cabbage and beans. Although the plating efficiency of Xcm on CCA was lower (59%) than on non-selective yeast extract peptone glucose agar (YPGA), its selectivity was significantly higher, averaging 60 and 82%, when isolating from banana fruits and soil, respectively. CCA was also superior when isolating Xcm from insect vectors, with selectivity of 48–75%, compared with 8–17% on YPGA. Xanthomonas campestris pv. phaseoli did not grow on CCA, while X. campestris pv. campestris and X. axonopodis pv. manihotis grew, but their colonies were smaller than those of Xcm. Twenty-nine out of 33 suspected Xcm strains isolated from plants, soil and insects using CCA were pathogenic when inoculated onto banana plants, indicating that CCA can be a reliable tool in isolating Xcm populations. The medium should prove useful in studies on ecology, epidemiology and management of the banana bacterial wilt pathogen that is currently ravaging bananas in East and Central Africa.